The ICRC in Central Africa in the end of the 20 th century : Case study of Cameroon, Congo-Brazzaville, RDCongo and Gabon, from 1960 up to 1999 - (:unkn) unknown (My University, 2015)
The International Committee of the Red Cross ICRC abstract is a humanitarian organization founded in 1863 by the Committee of five Swiss citizens: Moynier, Henry Dunant, Guillaume Dufour, Louis Appia, ThéodoreMaunoir. Creates the basis for the relief and assistance to victims of war, an initiative of Henry Dunant from a memory of the War of Solferino, the ICRC will extend its scope after the Geneva Convention of 1949. In Indeed, the ICRC is the NGO most represented in the world and it is appropriate that it was price-Nobel Peace Prize in 1901 awarded to Henri Dunant, in 1917, 1944, 1963 for his effort during the different conflicts, but also the Balzan Prize for humanity, peace and brotherhood among peoples in 1996. It was established gradually in all continents after the Second World War. Before that, she was a mostly European NGOs. In Central Africa, the delegation of the International Red Cross is based in Yaounde, Cameroon and includes the Central African countries such as Congo, DR Congo, Gabon, Equatorial Guinea and Sao Tome. In these countries the work of the ICRC varies Humanitarian needs of each other. The more a country is at war, most of the ICRC's intervention is important. This procedure is done in accordance with the rules established in the various Geneva Conventions, the Hague and many others. Of these conferences was born on international humanitarian law that codifies the ICRC's work in the field, especially in time of war, but also those of other NGOs, including UN entities. International law is respect for human rights and the environment in times of armed conflict. Thus the ICRC's work in Central Africa was greater in Democratic Republic of Congo and Gabon, which remained without military conflicts since 1960, starting date of our chronological terminal. The countries that are the subject of our study experienced various vicissitudes: Bakassi war for Cameroon, the civil war in Congo Brazzaville and war multifaceted ending in the D
Keywords: African Research